Characteristics of qualitative and quantitative properties of chicken village in the Sub-District Lasusua, North Kolaka District - Nafiu, La Ode; Abadi, Musram; Wati, Inra (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2020)
The purpose of this research is to know the characteristics of the qualitative and quantitative properties of village chicken in the Lasusua sub-district of North Kolaka district. The research was conducted in December 2018 to January 2019 in Lasusua sub-district of North Kolaka district. The variables observed in this study are qualitative and quantitative properties. The results are shown that both males and females of village chicken are dominated by colored fur colors, Columbian fur patterns, lauric fur patterns, and golden fur flicker. Color White/Yellow shank and a single shape Ginger. The average body weight of chickens 1,681.92 grams and females 1,305.45 grams. Long Shank Rooster 9.97 cm while females 8.34 cm. Tibia length 9.70 cm in males, 9.37 cm in females. The femur length is 13.07 cm in males and 11.87 cm in females. The length of the wingspan is 14.44 cm and females 12.49 cm. Male circumference 30.50 cm and female 29.59 cm. Male back length 14.17 cm and females 12.23 cm. Duration of the lung in males 1.96 cm and 1.94 cm in females.